Методика розрахунку розподілу тиску по довжині газопроводу при нестаціонарному режимі руху газу - Лесовой, Л.; Близняк, Л. (Видавництво Національного університету “Львівська політехніка”, 2004)
The method of definition of distribution of pressure on gas pipe-line when unsteady condition of movement of natural gas is worked out. The finite-difference method in order to solve the system of differential equations is used.
Keywords: 681.121